Characterization of the Existence of Morphology Endophyte Bacteria of Garlic (Allium sativum L.) with Plant Growth Promoting Rhizobacteria (PGPR) in the Highland Areas - Yelni, Gusni; Kasim, Musliar; Hayati, P.K. Dewi; Hervani, Dini (Akta Agrosia, 2024)
Utilization of Plant Growth Promoting Rhizobacteria (PGPR) is a strategy to increase the growth and yield of local garlic varieties. Bacteria contained in PGPR can act as ZPT and as biological fertilizer. This research aimed to determine the characteristics and presence of bacteria on the roots of garlic plants after PGPR application and to see the growth and yield of the best situs garlic varieties in the highlands. Isolation of garlic root endophytic bacteria was taken from applying PGPR in garlic cultivation in the highlands. The experiment used a randomized block design with treatments of Lumbu Putih, Lumbu Kuning, Lumbu Hijau, and Jangkiriah Adro garlic varieties, with 12.5 ml.L-1 of PGPR. Observations included plant height, bulb weight, number of colonies, and macroscopic form of bacteria. The research results showed that the highest number of endophytic bacterial colonies was found in the root isolates of the non-PGPR Lumbu Putih variety, namely 225 colonies. After administering PGPR, the highest number of bacteria was found in Lumbu Kuning root isolates, namely 200 colonies. The morphological characteristics of the bacterial colonies in the six isolates were round, wavy, convex, and raised, jagged edges, raised and flat, and the color was yellowish white. The Jangkiriah Adro variety had the best growth in plant height and bulb weight per plant compared to the Lumbu Putih, Lumbu Kuning, and Lumbu Hijau varieties. Keywords: characterization, colony, endophytic bacteria, garlic varieties, isolation